Pediatricians’ Competence in Prevention, Risk Determination or Detection of Suicidal Behavior in Children: Cross-Sectional Survey Study - Anna Y. Basova; Marina A. Bebchuk; Natalia V. Ustinova; Leyla S. Namazova-Baranova; Kamilla E. Efendiyeva; Elena A. Vishneva (Вопросы современной педиатрии)
Background. Child and adolescent suicides remain one of the most painful public issues. The COVID-19 pandemic has aggravated this topic as the number of suicides among children population has increased in this period. Research and practice guidelines identify the leading role of primary care physicians in the prevention, identification, and routing of patients with suicidal behavior. At the same time, there were no studies on pediatricians’ competence in the field of suicides.Objective. The aim of the study is to study pediatricians’ competence in prevention, risk determination or and detection of suicidal behavior.Methods. Cross-sectional study was conducted with the usage of original electronic questionnaire aimed on identifying the level of pediatricians’ competence in evaluating suicidal behavior in children. Questionnaire included 18 questions.Results. We have received 208 electronic questionnaires. 97.1% of specialists have confirmed that they evaluate emotional status of their patients during admission. During admission: 86.1% of specialists have considered the characteristics of children appearance, facial expression, voice intonation, 65.4% — have asked questions about mood, 62.5% — have interviewed parents. 98.6% of specialists pay attention to the presence of self-inflicted injuries marks, 88.4% — ask about the origin of these injuries. Only 36.1% of respondents ask patients about suicidal thoughts, intentions, or actions. Only 69.3% of specialists are ready to refer their patients to psychologist, and 51.7% — to psychiatrist.Conclusion. Even though most surveyed pediatricians notice signs of suicidal intent (low mood, self-inflicted injuries), they avoid discussing the topic of suicide during admission. Increasing the competence of pediatricians should be aimed on destigmatisation in the field of mental health, increasing the knowledge level, and developing practical skills in working with children with suicidal behavior.